Karakteristik Geomorfologi dan Stratigrafi Daerah Lambak , Kecamatan Ratatotok, Sulawesi Utara - Kakambong, Stela; Rachmadhan, H.D. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
This study was conducted in Lambak District, Ratatotok District, Southeast Minahasa Regency, North Sulawesi, to identify geomorphological and stratigraphic characteristics that reflect the complex geological history of the area. The methods used include geomorphological mapping, field observations, and petrographic analysis. The study area has two main geomorphological origins: structural and denudational. Structural forms include hills controlled by geological structures such as faults and folds, while denudational forms are dominated by hills resulting from intensive erosion processes. The stratigraphy of this area includes alluvial units, limestone (packstone and crystalline), and andesite intrusions. These units show a geological history that is closely related to tectonic and volcanic activity in the Sangihe magmatic arc during the Middle Miocene. The river drainage patterns in the study area, such as parallel, sub-dendritic, and trellis patterns, are strongly influenced by the geological structure and lithology of the rocks. The results of this study provide an important contribution to understanding the potential of geological resources, including mineralization and groundwater, as well as mitigating the risk of natural disasters such as landslides and tectonic deformation. The data produced is expected to support sustainable exploration of natural resources in this region.